Mechanical ventilation : physiology and practice - Kreit, John W. ([New York] : Oxford University Press, 2017)
This title provides students, residents, fellows, and practicing physicians with a clear explanation of essential physiology, terms and acronyms, and ventilator modes and breath types. It describes how mechanical ventilators work and explains clearly and concisely how to write ventilator orders, how to manage patients with many different causes of respiratory failure, and how to 'wean' patients from the ventilator.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 20, 2017).
Keywords: Respirators (Medical equipment); Artificial respiration